The combination of bortezomib, melphalan, dexamethasone and intermittent thalidomide is an effective regimen for relapsed/refractory myeloma and is associated with improvement of abnormal bone metabolism and angiogenesis - Terpos, E.; Kastritis, E.; Roussou, M.; Heath, D.; Christoulas, D.; Anagnostopoulos, N.; Eleftherakis-Papaiakovou, E.; Tsionos, K.; Croucher, P.; Dimopoulos, M.A. (Leukemia, 2008)
This phase 2 study aimed to determine the efficacy and safety of the combination of bortezomib, melphalan, dexamethasone and intermittent thalidomide (VMDT) and its effect on bone remodeling and angiogenesis in relapsed/refractory myeloma. Bortezomib (1.0 mg/m2) was given on days 1, 4, 8, 11, oral melphalan (0.15 mg/kg) on days 1-4, whereas thalidomide (100mg per day) and dexamethasone (12 mg/m2) were administered on days 1-4 and 17-20 of a 28-day cycle, for four cycles. Patients without disease progression continued for up to eight cycles. VMDT effect on bone remodeling was evaluated by measuring osteoclast regulators (soluble receptor activator of nuclear factor-κ B ligand/osteoprotegerin ratio, osteopontin, macrophage inflammatory protein-1α), dickkopf-1 protein, bone resorption and formation markers, whereas its effect on angiogenesis was assessed by measuring serum vascular endothelial growth factor, angiogenin, angiopoietin-2 and basic fibroblast growth factor, after four cycles and at the study end. A total of 62 patients were enrolled. The overall response rate was 66%: CR 13%, vgPR 27% and PR 26%. Median time to response was 35 days and median time to progression was 9.3 months. Common adverse events included cytopenias, peripheral neuropathy and infections. No patient experienced deep-vein thrombosis. VMDT reduced angiogenic cytokines, osteoclast regulators, dickkopf-1 and bone resorption. We conclude that VMDT with intermittent thalidomide is an active and well-tolerated regimen for relapsed/refractory myeloma, affecting abnormal bone remodeling and angiogenesis.